Mechanical carrier of bacterial enteric pathogens by Chrysomya megacephala (Diptera: Calliphoridae) in Chiang Mai, Thailand - Sukontason K. (2014)
Chrysomya megacephala was studied regarding its mechanically bacterial carrier in urban areas of Chiang Mai, northern Thailand. Fifty-six adult flies were randomly collected using sweep insect net during April-May, 1999 from 3 fresh food markets and examined for bacteriological isolation. Among them, 49 flies (87.5%) were bacterial carriers. The total 22 bacterial species and 8 groups were isolated. Three species previously reported as the bacterial enteric pathogens causing diarrheal disease were isolated from 5 flies, ie Aeromonas hydrophila, Edwardsiella tarda and Vibrio cholerae non-01, with their prevalence rates in flies being 3.579, 1.79% and 3.57%, respectively. Five possible bacteria enteric pathogens, ie Aermononas sobria, Citrobacter freundii, Escherichia coli, Providencia alcalifaciens and Pseudomonas aeruginosa, were isolated from 21 flies with the prevalence rates in flies being 5.34%, 3.57%, 26.79%, 7.14% and 1.79%, respectively. The bacterial load isolated from all 3 pathogenic species was entirely found more than 10 colony per fly, indicating the high chance for disease transmission via this fly species. C. megacephala may play the possible and/or important role of bacterial enteric pathogens transmission, thereby promoting the public health personnel for sanitation improvement in fresh food markets and fly control management in these particular areas.